Promoting Youth.SG : an integrated marketing communications approach - Ang, Yiying (2008)
How an integrated marketing communications approach was employed in increasing the awareness of Youth.SG and attracting visitors to the web portal. Evaluative research on the outcomes measures the success of the approach and leads to discussion for future implications and recommendations.